Influence of temperature, pressure, and cooling rate during hot isostatic pressing on the microstructure of an SX Ni-base superalloy. (5th May 2016) - Mujica Roncery, L.; Lopez-Galilea, I.; Ruttert, B.; Huth, S.; Theisen, W.
Abstract: This work investigates the application of hot isostatic pressing for heat treatment of the single-crystal Ni-base superalloy ERBO/1. Recent progress regarding incorporation of quenching within hot isostatic pressing enables heat treatments to be performed so that the microstructures can be frozen at a desired point. The influence of the temperature, pressure, and cooling method (quenching, natural convection, and slow cooling) as well as the cooling rate after solutioning-HIP treatment on pore densification and γ / γ ′-morphology was measured. Temperatures above γ ′-solvus resulted in a greater efficiency of the porosity reduction. At super-solvus temperatures, pressures above 75 MPa are sufficient enough to annihilate the porosity. The cooling rate after HIP-solutioning treatment has a major influence on the γ ′-particle size and shape. Quenching with 45–20 K/s at 100 MPa leads to high number density and monomodal distribution of γ ′-particles with sizes around 140 nm. In contrast, slow cooling rate of 0.33 K/s leads to γ ′-precipitate sizes of 720 nm. Moreover, an integrated heat treatment at 100 MPa, which consisted of solutioning and aging in the HIP, was successfully applied. It led to smaller γ ′-particle sizes and narrower γ -channels compared to the conventionally heat-treated material and also almost no porosity. Graphical Abstract: Highlights: A hot isostatic press with the ability to quench was used for the heat treatment of a single-crystal superalloy. The influence of temperature, pressure, and cooling rate on the microstructure was investigated. An integrated heat treatment under pressure consisting of homogenization and aging was successfully applied. The microstructure from the integrated heat treatment has high potential to improve the mechanical properties of superalloys.